The Majority’s Shackles: Societal Conflict and Development in the Establishment of Worship Places in Indonesia - Mahmudi, Mukh. Imron Ali; Anam, M. Syaeful (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This article aims to analyze the problems of establishing worship places in Indonesia and the potential for the development of religious harmony. The previous study explained that the issue of establishing places of worship in Indonesia had been accommodated in the Joint Regulation of the Minister of Religion and the Minister of Home Affairs (PBM) Number 9 and 8 of 2006 concerning the maintenance of religious harmony, empowerment of spiritual harmony forums, and the establishment of houses of worship. Researchers collected data through interviews and document studies of various cases related to conflicts over places of worship in Indonesia. This study uses a conceptual approach to developing the essential elements of sociology and the Strengths Weakness Opportunity Problem Action (SWOPA) analysis method to analyze the root causes and develop alternative policies to improve conflicts over the construction of places of worship in Indonesia. This study indicates that regulations regarding the establishment of houses of worship are used as a means of dialogue and become a legitimation to complicate and exclude the process of establishing houses of worship for minorities from various religions. In addition, the structural, cultural, and processual aspects that exist in the community are essential to be managed to minimize the occurrence of conflict. Stakeholders can also consider this analysis to build inclusive inter-religious relations.